2018
DOI: 10.1186/s13071-018-2932-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole body transcriptomes and new insights into the biology of the tick Ixodes ricinus

Abstract: BackgroundIxodes ricinus is the most important vector of tick-borne diseases in Europe. A better knowledge of its genome and transcriptome is important for developing control strategies. Previous transcriptomic studies of I. ricinus have focused on gene expression during the blood meal in specific tissues. To obtain a broader picture of changes in gene expression during the blood meal, our study analysed the transcriptome at the level of the whole body for both nymphal and adult ticks. Ixodes ricinus ticks fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Functional classification of most typical transcription was linked to cuticle formation and chitin metabolism as well as to the activation of blood-meal processing enzymes, all in response to a blood meal. These findings were anticipated and are in line with previous observations [30,31,33,75].…”
Section: Feeding-responsive Transcriptssupporting
confidence: 93%
See 2 more Smart Citations
“…Functional classification of most typical transcription was linked to cuticle formation and chitin metabolism as well as to the activation of blood-meal processing enzymes, all in response to a blood meal. These findings were anticipated and are in line with previous observations [30,31,33,75].…”
Section: Feeding-responsive Transcriptssupporting
confidence: 93%
“…Several transcriptomic studies were focusing on molecules that might directly influence feeding, such as haem utilization in ticks [27] or arthropod proteases, both being essential factors enabling a haematophagous life strategy [28]. Transcriptional regulation of the entire life-cycle, controlling tick ontogenesis and development has not been fully covered to date and existing research has only focused on a specific organ [29] or a life stage [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 55 unigenes on carbohydrate metabolism were differentially expressed (35 in F tick group, 9 in H tick group and 11 in M tick group), covering biological process such as carbohydrate phosphorylation, protein glycosylation, glycogen catabolic process, galactose metabolic process. The results indicated that the up-regulated unigenes encoding carbohydrate-metabolizing enzymes were similar with the genes identi ed in the transcriptomes of Ixodes ricinus [67], Haemaphysalis ava [31], Dermacentor variabilis [68], and in Argasidae of Ornithodoros moubata [41] and Ornithodoros erraticus [60]. According to the annotations, the up-regulated unigenes were associated with the metabolism and transport of several carbohydrates including glucose, fructose, mannose, galactose, maltose, idose, malate and chitin (Table 4).…”
Section: Differential Gene Expression Pro Lessupporting
confidence: 52%
“…ncbi.nlm.nih.gov/genbank/) or the web sites of each publication (for example: https://parasitesandvectors. biomedcentral.com/articles/10.1186/s13071-018-2932-3 (Charrier et al, 2018). Among tick species shown in Fig.…”
Section: An Overview Of Omics Approaches In Tick Researchmentioning
confidence: 99%